JURIDICAL ANALYSIS OF THE IMPLEMENTATION OF DIRECT LICENSING AS AN ALTERNATIVE MECHANISM FOR MANAGING SONG COPYRIGHT ROYALTIES - Raden Handiriono (Hukum Responsif, 2026)
The changing music industry ecosystem, increasingly driven by digital technology, has created new challenges for songwriters in copyright and royalty management. The collective management system, which has been the main instrument for distributing royalties, is often considered inefficient and non-transparent, and has not fully provided creators with space to control their economic rights independently. In the midst of this dynamic, a direct licensing mechanism has emerged as an alternative that allows creators to grant users direct permission to use musical works without intermediaries. This study seeks to analyze the role and implementation of direct licensing within Indonesia's copyright law framework and to provide an optimal regulatory approach to guarantee legal certainty and the effective safeguarding of authors' economic rights in the future. The study employs a normative juridical methodology with a conceptual framework, qualitatively examining laws and regulations through the interpretation of fundamental principles of copyright law. The study's findings indicate that direct licensing rests on a robust legal legitimacy foundation, grounded in the exclusive rights of artists and the concept of freedom of contract; nonetheless, it faces challenges due to the absence of explicit laws and insufficient support structures. To realize a fair and effective system, it is necessary to establish a legal mechanism that recognizes direct licensing as a legal instrument that operates alongside collective management, and to accompany it with measures to strengthen transparency, digital recording, and the protection of electronic contracts.